Perancangan User Interface Sistem Informasi Alumni Menggunakan Metode Webuse Dan User Centered Design - Agung Nugroho Pramudhita; Putra Prima Arhandi; Ferina Bayu Sukmadewi (Jurnal Teknologi Informasi dan Terapan, 2022)
Alumni Information System is a system that facilitates data collection process and obtains information about alumni. Based on results of interviews with several alumni who just graduated in 2020 at State Polytechnic of Malang, results were obtained, they had problems accessing website, such as updating data, searching for alumni data, and registration for graduation ceremony. Based on results of online survey to several alumni of State Polytechnic of Malang, problems were founded in content organizing, ease of reading content, navigating links, UI/UX, and website effectiveness. To make website with interface is user friendly, design improvements are needed to provide recommendations for problems that arise. User Centered Design method was chosen to design user interface according to user experience and webuse was chosen because it focuses on evaluating usability of website and helping web designers and developers based on responses given by visitors. Results Both of evaluation from UI design in content organizing & readability category and navigation & links category are 0.85 with an “Excellent” usability level. In user interface design category result is 0.86 with an “Excellent” usability level, and performance & effectiveness category result is 0.81 with an “Excellent” usability level. So that entire webuse category has increased.